Pengaruh Kedisiplinan dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Departemen Facility Care (K2) PT. Angkasa Pura Support - Delia Sri Wahyuni; Ujang Suherman; Thomas Nadeak (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Employee performance in airport service support environments faces distinctive challenges due to high discipline requirements and intensive operational pressures, while empirical studies focusing specifically on discipline and motivation within airport support services remain limited. A quantitative approach was employed using a saturated sampling technique involving 60 employees from the Facility Care (K2) Department of PT Angkasa Pura Support. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with classical assumption testing. The findings indicate that work discipline has a positive and significant effect on employee performance, while work motivation also contributes significantly. Simultaneously, both variables moderately explain variations in employee performance, highlighting the importance of combining internal motivational factors with adherence to structured work systems in airport service contexts. These results reinforce human resource management theories and provide contextual contributions to high-risk service sectors. Practical implications emphasize the need to strengthen discipline systems through effective supervision and to enhance motivation through reward mechanisms and organizational support in order to achieve sustainable performance improvement.